2000
DOI: 10.1002/(sici)1099-1263(200001/02)20:1<21::aid-jat623>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of melatonin on cell proliferation in a colon adenocarcinoma line

Abstract: The effect of melatonin on inhibition of cell growth was studied in CT‐26, a murine colon carcinoma‐derived cell line. Cells growing in exponential phase were exposed to low (10−7–10−10 M) and high doses (1, 2 and 3 × 10−3 M) of melatonin during 24 h. Synthesis of DNA was measured by 5‐bromo‐2′‐deoxyuridine incorporation. There was no effect at low doses, but a statistically significant correlation was found between the decrease in DNA synthesis and the dose of melatonin used (r = −0.52, P < 0.001). This impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 18 publications
4
69
0
Order By: Relevance
“…However, others were not able to confirm these preliminary results [86,87], even when an inhibitory effect on tumor growth was observed at high melatonin concentrations. No effect of melatonin on apoptosis was documented by Lewinski et al [88] or by Garcìa-Navarro and co-workers [89] in HT-29 colon cancer cells.…”
Section: Melatonin In Gastrointestinal and Colon Cancersmentioning
confidence: 99%
“…However, others were not able to confirm these preliminary results [86,87], even when an inhibitory effect on tumor growth was observed at high melatonin concentrations. No effect of melatonin on apoptosis was documented by Lewinski et al [88] or by Garcìa-Navarro and co-workers [89] in HT-29 colon cancer cells.…”
Section: Melatonin In Gastrointestinal and Colon Cancersmentioning
confidence: 99%
“…104 The effect of melatonin on inhibition of colon carcinoma cell growth was studied in CT-26 cells, a murine colon carcinoma-derived cell line. 105 Although melatonin had no effect on cell growth at low doses, a statistically significant and progressive suppression of DNA synthesis was found as melatonin doses increased (the percentage of inhibition being 1 mM, 22%; 2 mM, 25%; 3 mM, 47%). 105 Inasmuch as no receptors were involved in the cell line selected, it was concluded that melatonin exerted its anti-proliferative action through a nonhormonedependent mechanism.…”
Section: Melatonin In Colorectal Carcinomamentioning
confidence: 99%
“…In CRC, melatonin inhibits cell growth and induces apoptosis in vitro [21,22,23] and in vivo [24]. Recently, it has been reported that melatonin decreases CSCs and dysplastic injuries in colon tissue [24].…”
Section: Introductionmentioning
confidence: 99%